Intraoperative transesophageal echocardiography: the roadmap for successful mitral valve repair - Mehta, Anand R.; Burbano-Vera, Nelson (Annals of Cardiothoracic Surgery, 2026)
Intraoperative transesophageal echocardiography (TEE) is crucial in defining a real-time imaging guide for a successful surgical repair of degenerative mitral valve (MV) disease. Three-dimensional TEE enhances the echocardiographer’s ability to delineate and communicate the pathology more precisely. It is an invaluable tool in guiding peripheral cannulation for minimally invasive and robot-assisted surgical valve repairs and is critical in determining the adequacy of repair and associated complications. As an imaging modality, TEE is an indispensable aid during mitral valve repair (MVR).